Nitrogen signaling and nuclear localization of the Aspergillus nidulans GATA transcription factor AreA. - Hunter, Cameron Creighton (Kansas State University, 2022)
Saprophytic fungi are responsible for the biodegradation and recycling of the majority of organic matter in nature; a process which allows for carbon and nitrogen to be reintroduced into the ecosystem. In order for this process to occur, fungi must have the ability to adapt quickly to changes in nutrient quality and availability within their environment. These rapid adaptations are achieved by the regulation of nutrient utilization gene expression. In Aspergillus nidulans the GATA transcription factor AreA activates transcription of nitrogen metabolic genes in response to nutrient availability. During nitrogen poor conditions (nitrogen sources other than ammonium and glutamine), AreA-dependent gene expression increases to activate alternative nitrogen nutrient utilization genes. When nitrogen sources become unavailable (nitrogen starvation conditions), expression of a subset of AreA-dependent genes greatly increases and AreA begins accumulating in the nucleus. Nuclear import of AreA appears to not be strongly regulated, unlike its Saccharomyces cerevisiae orthologs, Gln3p and Gat1p, which are regulated by Ure2p in response to sufficient intracellular nitrogen. In contrast, AreA nuclear localization is regulated by blocking its nuclear export via the exportin CrmA in response to nitrogen starvation. Previous research demonstrated that a hemagglutinin (HA) epitope-tagged AreA, AreA[superscript HA], begins transitioning from the cytoplasm to the nucleus when cells become nitrogen starved, and after 4 hours of nitrogen starvation, AreA[superscript HA] is completely localized to the nucleus. This increase in nuclear localization parallels the activity increase observed during nitrogen starvation in AreA-dependent reporter gene assays. The research presented in this dissertation aims to understand the mechanisms and pathways involved in regulating the function and intracellular dynamics of the GATA transcription factor AreA as it pertains to nitrogen metabolism in Aspergillus nidulans. In Chapter 3, we identify the sequences within the AreA protein that are critical for import of AreA into the nucleus. We analyze the role of the six proposed Nuclear Localization Sequences (NLS)s within AreA in their native context by using in-frame deletions or point mutations of the NLSs separately and in combination. We also determine which NLSs are sufficient for nuclear localization when fused to Green Fluorescent Protein (GFP). Both of these approaches demonstrate that the multiple NLSs play redudant roles contributing to AreA nuclear localization. In Chapter 4, we move our investigation to the mechanism of AreA nuclear accumulation by investigating the role of the [alpha]-importin KapA in AreA nuclear import and the effects SumO, the small ubiquitin-like modifier, has on the subcellular localization of both KapA and AreA. We also analyze the effects of nutrient signaling on AreA nuclear localization. We identify components of the Target of Rapamycin (TOR) signaling pathway as well as the autolysis pathway, via the transcription factor XprG which mediates aspects of starvation, that play roles in regulating AreA nuclear accumulation. In Chapter 5, we investigate how nitrogen is sensed by assessing the effects of ammonium concentration, the role AreA DNA binding mutants have on AreA nuclear accumulation, and how nitrogen metabolic mutants affect colonial growth and AreA nuclear accumulation on different nitrogen sources. Overall, this work advances our understanding of nitrogen regulation in fungi by the key transcription factor AreA by identifying key components that mediate and regulate AreA nuclear localization.
Keywords: Nuclear localization signals; Transcription factor; Aspergillus nidulans; Nitrogen regulation; AreA; Nuclear import